Seismic Performance of Existing Building Retrofitted with VSL-Gensui Damper - Pamuda Pudjisuryadi; Benjamin Lumantarna; Tjhai Ferlinda Hermawan; Teddy Tirta Gunawan (Institute of Research and Community Outreach - Petra Christian University, 2018)
Buildings designed using older code should be checked against the higher demand required by newer code. In this study, performance of Building T of Petra Christian University, Surabaya, Indonesia, which was designed with older Indonesian Seismic Code (PPTGIUG 1983) is investigated. The effectiveness of VSL-Gensui Damper application is also investigated as an effort to enhance the performance of the building. Nonlinear time history analysis was conducted to analyze the building. Spectrum consistent ground acceleration generated from El Centro 18 May 1940 North-South component in accordance to current seismic code was used for analysis. The result shows that the existing building cannot resist the demand specified by current code (SNI 1726:2012) as some frame element failures are detected. The performance is greatly enhanced after installation of VSL-Gensui Dampers. Roof story drift and displacement decreased as much as 9% and 14%, respectively as compared to existing building, and structural element failures were no longer observed.